Analisis Tata Kelola dan Evaluasi Teknologi Informasi Menggunakan Framework COBIT 2019 di Sekolah X - Harahap, Fardiansyah; Wasilah (Jurnal Informatika, 2025)
The utilization of Information and Communication Technology (ICT) in education involves various systems, and if not managed well, can pose serious risks such as data damage and theft, misuse of data, and data interception. School X is one educational institution that harnesses ICT in various aspects, but its implementation is not yet optimal and some systems are ineffective. Therefore, this research aims to analyze and evaluate the existing information technology governance at this school. The study employs COBIT 2019 as a framework to design, monitor, and enhance the capabilities of information technology governance. COBIT 2019 provides comprehensive guidelines to ensure aspects such as processes, organizational structures, culture and behavior, information, services and infrastructure, principles and policies, as well as skills and competencies of human resources are well aligned. The objective of this research is to analyze and evaluate the information technology governance at School X, and to seek solutions for the ineffective and inefficient utilization of information technology. The research results include recommendations for the design of an IT governance system, specifically addressing APO09, BAI10, DSS01, DSS02, DSS03, and DSS04. APO09, DSS01, and DSS02 domains are at capability level 2, BAI10 and DSS04 domains are at capability level 3, while the DSS03 domain is at capability level 4. Applying the recommendations from the COBIT 2019 analysis at School X is expected to greatly enhance the efficiency and effectiveness of its IT governance.